Remarks on the phonology of a south-western Karaim translation of the latter prophets - András, Anita (Vilnius University Proceedings, 2024)
The present paper focuses on the only available South-Western Karaim translation of the Latter Prophets, registered under the accession number ADub.III.83. Alongside a concise overview of the manuscript and its copyist, Jeshua Josef Mordkowicz, the paper offers a brief analysis of the Modern South-Western Karaim traits displayed in the language of the manuscript.